2023
DOI: 10.1007/s12032-023-02149-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of anticancer effect of gambogic acid on gastric signet ring cell carcinoma

Abstract: BackgroundGambogic acid has demonstrated inhibitory effects on the growth of various cancer cell types, such as breast cancer, pancreatic cancer, prostate cancer, lung cancer, and osteosarcoma. This study aims to investigate the antiproliferative activity of Gambogic acid on SNU-16 cells derived from gastric signet ring cell carcinoma and elucidate the underlying mechanisms. Material and MethodsThe cytotoxic effect of gambogic acid was evaluated in SNU-16 cells by treating them with different concentrations of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…GA demonstrated the ability to induce apoptosis in esophageal squamous cell carcinoma cells in a dose-dependent manner, which was achieved by reducing Bcl-2 levels and increasing the levels of Bax, cleaved-PARP1 and cleaved caspase 3/9 [44]. In a study involving gastric signet ring cell carcinoma, GA revealed an upregulation of cleaved caspase 3, Bax, and cleaved PARP, along with a downregulation of Bcl-2 [45]. GA-loaded NLCs have also been reported to inhibit tumor and metastasis growth, potentially due to alterations in MMP-9, BCL-2, and E-cadherin levels [46], and GA has been found to influence the expression of Bax, caspase 3, and caspase 9 in human osteosarcoma [47].…”
Section: Discussionmentioning
confidence: 97%
“…GA demonstrated the ability to induce apoptosis in esophageal squamous cell carcinoma cells in a dose-dependent manner, which was achieved by reducing Bcl-2 levels and increasing the levels of Bax, cleaved-PARP1 and cleaved caspase 3/9 [44]. In a study involving gastric signet ring cell carcinoma, GA revealed an upregulation of cleaved caspase 3, Bax, and cleaved PARP, along with a downregulation of Bcl-2 [45]. GA-loaded NLCs have also been reported to inhibit tumor and metastasis growth, potentially due to alterations in MMP-9, BCL-2, and E-cadherin levels [46], and GA has been found to influence the expression of Bax, caspase 3, and caspase 9 in human osteosarcoma [47].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the capacity of GA to promote apoptosis and autophagy is thought to be the cause of its antiproliferative action against cancer cells. 33 …”
Section: Anticancer Activities Of Gambogic Acidmentioning
confidence: 99%